건강불평등에 대한 개념분석 - 권정옥(Jeong Ok Kwon); 이은남(Eun Nam Lee); 배선형(Sun Hyoung Bae) (Kanho Haengjŏng Hakhoe chi = The journal of Korean Nursing Administration Academic Society, 2015)
Purpose: The purpose of this study was to explore ways to define the concept of health inequality. Methods: The concept analysis process by Walker and Avant was used to clarify the meaning of health inequality. Results: Defining attributes of health inequality included differences in health status between individuals or groups, infringement of fundamental rights to health, unfair use of medical services, and social discrimination. The antecedents of health inequality included differences in demographic characteristics (age, gender, education, occupation, residential location), limitations in accessibility to health care, and social exclusion. Consequences of health inequality were increased costs for medical care, decreased health-related quality of life, and lack of ability to cope with health problems resulting in crisis situations, increases in morbidity and mortality, and shortening of life span. The concept was clarified through presentation of model, borderline, related, and contrary cases. Conclusion: Results of this study can be used to guide the direction of future studies through concept analysis in which conceptual attributes in the context of health inequality are examined. Also, based on the result of this study, development of standardized tools to measure health inequality is recommended as well as development of educational programs to reduce health inequalities.